Critiques on the Ideologies of Contemporary Bedhayan Dances - Sawitri, Sawitri; Sudardi, Bani; Abdullah, Wakit; Chaya, Nyoman (KOMUNITAS: International Journal of Indonesian Society and Culture, 2017)
This present paper provides a descriptive analysis toward a traditional court dance called Bedhaya, one of the cultural products of the Javanese community in Surakarta which evolved into its modern version Bedhayan due to the flow of global culture. By applying the theories of hermeneutics, ideology, aesthetics and Semiotics, the data are inferred according to the purposed questions. The inquiry is directed to infer the factors encompassing Bedhaya dance such as its emergence and the development, relationship with the existence and its role in the society, the relationship with systems within the society or with various interests. The results as inferred from the data obtained views in looking at the development on the classical dance of Bedhaya into Bedhayan left worthy of critical assessments. The reality of Bedhayan dance in the view of art as an ideology, from the outside, appears that the choreograhers/artists can freely express their creative ideas in the context of the fight agains the classical culture which is strongly enacted by the myths and power of the rulling king. However, it should be noted that Bedhayan dance artists which have managed to bring the classical bedhaya dance out of the walls of the Kraton also in essence always work in the confines of the iron curtain of a creativity called ‘ideology’. Whether consciously or not, being forced or sincere in living it, these choreographers actually fall into the life orientation which solely concerns the fulfillment of material needs.